Nursing as a profession practiced in the future - opinion of junior high school students - Monika Teresa Pierzak (Kazimierz Wielki University, 2017)
Introduction Nursing is a profession of public trust, which, because of the nature of work with another person, is subjected to constant evaluation. Aim Evaluation of the perception of the profession of nurse by the youth of the matura classes. Material and methods The study was conducted from February to April 2016 in randomly selected post-gymnasium schools. The questionnaire survey was used for the study. Results The study involved 105 students in the matura classes, among them 77 were women, which constituted 67% and 35 men, which is 33% of the total population studied. Nineteen were 64 of them, 61% of the total, and 41 of them, 39% of the respondents. Research shows that young people consider the profession of Nursing / Nurse to be a profession of interest to such an answer, more than half of the respondents 54.3%. Only 28.6% of respondents consider the profession of nurse to be unattractive. Respondents indicated that the majority of the high school students surveyed were 54 (51.4%) who did not want to work as a nurse / nurse, only 27 (25.7%) of the respondents expressed their willingness to work in the profession, 24 ( 22.9%) people abstained from the answer. The strange fact is that young people in most professions of nurses find it interesting. Conclusions According to junior high school students, the profession of nurse / nurse is an interesting profession. The person who is a future trainee should be qualified; Sense of responsibility, communicativeness, theoretical and practical knowledge. The profession of the nurse of the examined youth is associated with the assistant, assistant doctor.